A Study on the Contribution of a Performance Marketing Intern to the Success of the Sleep Company - Shendre, Payod (ATLAS SkillTech University, 2025)
This internship report, "A Study on the Contribution of a Performance Marketing Intern to the Success of The Sleep Company," will present in detail my rewarding experience as an intern in Performance Marketing at The Sleep Company. This summer internship was pursued under my second-year MBA curriculum at Atlas Skilltech University and was guided by Prof. Ameya Ambulkar. During the internship, I was actively able to contribute to several performance marketing initiatives, which included paid advertising, and social media marketing campaigns. It synthesizes key insights and practical knowledge, highlighting my contribution toward customer acquisition, brand awareness, and, by extension, business performance. Performance marketing in the digital era is a very serious affair, and it goes without saying how this report will combine my internship experience with the requisite skill set that would help in such effective employments of strategy. This executive summary tries to provide an overview of the detailed findings and reflections of the subsequent sections of this report to the readers to help them understand the value of this transformative internship experience at The Sleep Company.
Project Report on A Study on the Contribution of a Performance Marketing Intern to the Success of the Sleep Company (2023-2025) Under the Guidance of Prof. Ameya Ambulkar
Keywords: Marketing; customer acquisition; brand awareness